Exports Trade and Economic Growth in Zanzibar - Suleiman, Salim Hamad (Archives of Business Research, 2018)
We examined the applicability of the Export-Led Growth hypothesis for Zanzibar using annual time series data during the period of 1985-2016. The estimation results obtained from the cointegration test and Granger Causality test within the framework of a Vector Autoregressive (VAR) model supported the Export-Led Growth hypothesis for Zanzibar. Our results indicate that the hypothesis causes economic growth and the existing of long-run relationship between clove export trade and economic growth. In addition, analysis of Impulse Response Function (IRF) suggests that a sudden economic growth rate and an increase in clove export positively impact others with exception to labour. However, the sudden increase in share of clove export will cause adverse effect to economic growth rate.